The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6611037
|View full text |Cite
|
Sign up to set email alerts
|

Development of 3-D ultrasound system for assessment of adolescent idiopathic scoliosis (AIS): And system validation

Abstract: Adolescent idiopathic scoliosis (AIS) is a common spinal disease and the prevalence of AIS is 2 to 4 % of the youngsters in the United States. Radiograph based Cobb's method is regarded as the gold standard. AIS patients normally have to undergo regular X-ray assessment every 4 to 6 months until skeletal maturity is reached. Because of radiation hazard, X-ray images cannot be taken frequently, and thus it is difficult to perform close monitoring for the disease progression and treatment outcomes. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…The results demonstrated that the new measurement method could provide reliable spine curvature measurement with performance comparable to that by X-ray Cobb's method. Unlike the previous method using landmarks observed in separate ultrasound B-mode images [13,[19][20][21], the proposed measurement method was to measure the spine curvature with the visualization of whole spine, reducing the measurement error and eliminating the searching of US B-mode images with corresponding bony features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that the new measurement method could provide reliable spine curvature measurement with performance comparable to that by X-ray Cobb's method. Unlike the previous method using landmarks observed in separate ultrasound B-mode images [13,[19][20][21], the proposed measurement method was to measure the spine curvature with the visualization of whole spine, reducing the measurement error and eliminating the searching of US B-mode images with corresponding bony features.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, freehand 3D ultrasound, combining conventional B-mode ultrasound with position sensor, has been advanced to overcome the limitations of 2D viewing of 3D anatomy [14][15][16][17][18][19][20][21]. The spine curvature was estimated through manually locating the transverse processes in some ultrasound images with 3D spatial information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that approximately 4% of adolescents between the ages of 10 and 18 have idiopathic scoliosis [1][2][3]. However, its pathogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative US could also supplement fluoroscopy-based procedures, such as pelvic fracture fixation [2,3]. In pediatric orthopaedics, Cheung et al [4] demonstrated the potential benefits of US imaging in routine checkups of scoliosis patients. Furthermore, in spine imaging, US bone surface extraction was shown to be promising for needle-insertion applications [5].…”
Section: Introductionmentioning
confidence: 99%